Prevalence of oculomotor, binocular vision anomalies and refractive error among children with cerebral palsy in WHO South-East Asia: A protocol of systematic review and meta-analysis - Radhika R P; Bhamini Krishna Rao; Shonraj Ballae Ganesh Rao; Nachiket Gudi; Shradha Parsekar; Revathy Mani (MethodsX, 2025)
Introduction: Children with cerebral palsy (CP) may experience a variety of visual abnormalities, which might hamper their daily activities. Most physical therapy for the CP population focuses on visual aspects, which postpone rehabilitation outcomes. Considering the significance of vision to the CP community, we aimed to conduct a systematic review of the prevalence of ocular abnormalities such as oculomotor abnormalities, refractive errors, and binocular vision anomalies in children with Cerebral palsy in the absence of eye injury in WHO South-East Asia region. Methods & analysis: This systematic review and meta-analysis protocol are reported as per the PRISMA- P and MOOSE guidelines. A complete search strategy will be framed using MeSH terms and the opinion of the subject expert. A detailed search on PubMed, the Cochrane Library, Scopus, Web of Science and CINHAL will be carried out to retract the data on the prevalence of visual problems in the CP population (age< 18 years), published in English between January 2010 and 2024. Covidence software will be used to manage data, screen records and extract the information. The Newcastle-Ottawa Scale will be used to evaluate the listed studies quality and risk of bias. RevMan V.5 will be used to analyse the data.